Evaluating Alternative Stock Option Timing Strategies - McGuigan, James; King, William R. (Journal of Financial and Quantitative Analysis, 1974)
For many years, the stock option has been an investment device used primarily by speculators and some “sophisticated” investors. During the past few years, much more attention has been paid to options by mutual funds, insurance companies, and conservative investors who previously showed little concern for this investment alternative. The opening of the Chicago Board of Trade's exchange for the trading of options will lead to even wider interest in the area.